Water Requirements of ‘Meyer’ Zoysiagrass for Survival and Recovery After Prolonged Drought - Mu Hong; Dale Bremer; Steve Keeley (Kansas Agricultural Experiment Station Research Reports, 2020)
Water restrictions on irrigation are generally not science-based and may cause irreversible damage to turfgrass or inadvertently waste water. The objectives of our study were to evaluate effects of minimum water applications to ‘Meyer’ zoysiagrass (Zoysia japonicaSteud.) on 1) turfgrass performance during prolonged dry downs; and 2) survival and recovery thereafter. Zoysiagrass was watered with 0, 5, 10, 15, 20, 25, and 30% reference evapotranspiration (ET) replacement for two months in two consecutive summers under an automated rainout shelter (excluded all rainfall) near Manhattan, KS. Results indicated that irrigation at 20 to 30% ET slowed the decline in zoysiagrass performance compared with no water inputs. Irrigation at 30% ET maintained zoysiagrass at>75 percentage green cover (PGC) in the first year, and even with no water inputs (0% ET) or irrigation at only 5% ET replacement, zoysiagrass recovered after full irrigation resumed. In the second year, irrigation at 30% ET maintained zoysiagrass at>25 PGC throughout the dry down and it recovered thereafter, but plots with no water inputs (0% ET) or irrigated with 5% ET replacement only recovered to 30–42 PGC after 50 days of full irrigation. Water restrictions during severe droughts may conserve more water and reduce turfgrass damage by limiting irrigation of zoysiagrass to 20–30% ET than by using traditional standards such as allowing irrigation for only one day per week.
Keywords: water conservation; water restrictions; lawn irrigation; warm-season lawn